Islamic Brokerage (Samsarah) in Contemporary Markets: An Empirical Analysis of Vehicle Transactions in Rural Indonesia - Nila Saadati; Ach. Faris; Zamzamil Fikri (Asian Journal of Law and Islamic Finance, 2025)
This study examines the implementation of Islamic brokerage (Samsarah) principles in vehicle transactions in Prenduan Village, East Java, Indonesia, analyzing its alignment with normative standards established in Fatwa DSN-MUI No. 151/DSN-MUI/VI/2022. Through qualitative investigation utilizing interviews with 12 participants, observation of 8 vehicle transactions, and document analysis, this research reveals how traditional Islamic commercial practices adapt to contemporary market contexts while maintaining claims to religious legitimacy. The findings demonstrate that Samsarah arrangements in rural Indonesia primarily manifest through verbal agreements that nonetheless satisfy substantive Islamic contractual requirements for clarity and mutual consent. Two dominant compensation structures emerge: fixed-amount commissions and variable compensation based on sale price surplus, both aligning with Islamic jurisprudential principles while reflecting practical market adaptations. While transparency practices concerning broker roles demonstrate strong alignment with Islamic ethical standards, vehicle condition disclosure exhibits variable implementation influenced by both religious principles and practical information constraints. Risk allocation follows a temporal division of responsibility that blends Islamic trust principles (amanah) with community norms, while dispute resolution prioritizes informal community-based mechanisms over formal religious institutions. This study contributes to theoretical understandings of Islamic financial intermediation by demonstrating the complex interplay between religious principles, market pragmatics, and community norms in shaping actual economic practices. The findings suggest that effective governance of Islamic markets requires sensitivity to existing informal institutions rather than exclusive reliance on formal regulatory frameworks, highlighting how Islamic commercial ethics may extend beyond minimal religious requirements through additional community-established ethical safeguards.